Thoughts on the Industrialization of Alternative Protein Foods - Haijuan Hu; Shouwei Wang; Yuxuan Li; Jinyuan Sun; Shilei Li; Yingying Li; Baoguo Sun (中国工程科学)
Alternative protein foods are obtained using biomanufacturing technologies such as synthetic biology and cell engineering; they are sustainable and efficient in synthesis. Promoting the engineering and industrialization of alternative proteins is crucial for developing new quality productivity and ensuring national food security in China. This study illustrates the development values of alternative protein foods from the aspects of intensified international competition, development of an all-encompassing approach to food, new quality productivity, and sustainable development. It also analyzes the development status of alternative protein foods in China and abroad from the scientific, regulatory, and industrialized perspectives. It was concluded that breakthroughs should be achieved in key technologies such as cell lines, serum-free media, dedicated bioreactors, high-efficiency screening and preparation of microbial chassis strains, and plant-based meat fabrication and flavoring. Meanwhile, it is necessary to establish food safety standards and regulatory frameworks, improve China’s independent research and production capacities of key elements, and expand sub-sectors of the industrial chain. Furthermore, targeted suggestions are proposed to accelerate the industrialization of alternative protein foods. This study is expected to provide references and inspirations for the research, practices, and supervision of alternative protein industrialization in China.